Artistic Heritage in the Globalization Era: A New Research Approach for Educational Contexts - Prieto, Antonio Félix Vico (International Journal For Research In Educational Studies, 2018)
The term globalization describes the acceleration of the integration of nations into the global system. For that reason, globalization influences are changing our cultural patterns, and we can evidence how young people no longer take an interest to own culture. In addition, less attention is paid to the development of the art of the country in its own unique way. Moreover, the architectural landscape, the painting, and the music all show the great influence of the phenomenon of globalization we are living today. These changes raise the relevance of preserving the general knowledge about heritage, focusing on the study of its origins. Additionally, if current generation is losing that entire cultural heritage, the question of in what way globalization is influencing the imagery of our time should be answered. Focused on the educational context and based on our previous experience, the making of an audio-visual production is revealed as a very powerful tool to solve this problem. It will focus on one side on the heritage renewal work itself and on the other had in the diffusion of the gained knowledge through audio-visual formats. This innovative proposal is without doubt one of the landmarks in this study. We believe in adding a new point of view. La Danserye is a documentary film educational project that illustrates the journey that Philip II made in the Netherlands between 1548 and 1551.The film shows a deep music research of La Danserye´s members ensemble based on works by Antonio de Cabezón and Tielman Susato.